A systems approach to circular economy transition: Creating causal loop diagrams for the Icelandic building industry - Agusta Thora Jonsdottir; Lara Johannsdottir; Brynhildur Davidsdottir (Cleaner Environmental Systems)
The circular economy is high on the political agenda as a solution to minimize raw material use and carbon footprints across socio-economic systems. Each country must follow its path to achieving circularity, and businesses must seek new types of sustainable and circular business models. This study aims to analyze the Icelandic building industry as a case study from a systems perspective to identify the systemic forces influencing the adoption of circular business models. The study formulates dynamic hypotheses regarding implementing circular strategies, represented as causal loop diagrams (CLDs). Following qualitative methods, including semi-structured interviews and group model building. The dynamic hypotheses proposed to explain the system's internal behavior that drives its dynamic around four critical problems: 1) Lack of the snowballing effect. 2) Lack of regulatory policies for improving environmental performance. 3) Lack of public demand for implementing circular strategies. And 4) A conservative culture within the industry. The study identifies a gap in the literature by highlighting the need to examine the dynamics between barriers in implementing circular strategies during the transition toward a circular economy rather than analyzing them in isolation. Its theoretical contribution lies in advancing the understanding of complex dynamics, enriching transition theory as it applies to circular economy transition. This approach also reinforces the business case for sustainability while aligning with stakeholder theory, offering a more holistic perspective on enabling systemic change. The study provides business leaders and policymakers with an analysis identifying actionable recommendations for regulatory reforms, supporting the transition toward a circular economy.